‘The fatherland perished in the frozen wastes of Russia’: West-Germans in search of the European soldier, 1940–1967 - Tattenberg, J (Taylor and Francis, 2019)
Although the European Union is today largely understood as the guarantor of peace and prosperity on the continent, a continued but neglected aspect of discourses of European integration has been military integration. The idea of a European army appealed in particular to West-German military elites. European military integration, they understood in part as a pragmatic response to technological and geopolitical developments. But they also sought to conceive of a way to safeguard both the West-German state and the Christian Occident from Bolshevik invasion. The solution was a European soldier, who embodied a set of masculine, Christian values. Such an image was a result of experiences gathered on the Eastern Front during the Second World War, which continued to shape the West-German military elite’s thinking about European integration into the late 1960s.